Challenges and Opportunities in the Implementation of School Literacy Movement at Senior High Schools in Bangka Belitung - Taufiq, M. Aries; Herza, Herza; Putri, Rahmi Eka; Ariksa, Jeri; Amalia, Resti (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
The purpose of this study was to examine the implementation of the School Literacy Movement (SLM) as well as its challenges in high schools in Bangka Belitung. The study combined a descriptive method with a qualitative approach. Principals, instructors, librarians, and a number of student representatives from grades X through XII from three schools in Kab. Bangka Barat were the subjects of this study. In order to gather data for this study, observation, interviews, and documentation were used. The study's findings demonstrated that the SLM program had not been executed at SMA/MA in Kab. Bangka Barat in the most effective way possible. This was evident from the inadequate preparatory phase, which prevented the SLM program from being implemented to its full potential. The implementation of this SLM remained hampered by a number of challenges, according to this study. These included students' low reading interest, the school's limited supply of reading materials, its lack of time to give students reading assignments, and its inconsistent application. Also, it had not been shown how important parents of students were to the success of this program.